Network File System Implementation on Computer-Based Exam - Sumarna -; Felix Wuryo Handono; Hafis Nurdin (Future Science, 2020)
In the world of education, exam is the final stage to evaluate the student abil-ity. The length of the correction process and the expensive cost of printing for manually exams are obstacles that often occurs when administering the ex-ams. Computer-based exams is an effort that is present to solve the problems, by using a computer, then the cost of printing documents and others can be minimized, besides that there is no need for manually correction time, be-cause when students finished the exam, the student's grades can be immedi-ately known. So many advantages are offered by computer-based exams but of course there are still problems that arise. The most common thing is the slow server in processing requests from clients when accessed together, in-creasing the number of servers using Network File Server is one of the efforts to correct the shortcomings of computer-based exams. Using Network File Server is expected to be able to overcome these problems.